Semen quality and Gonadometric assessment of the male Wistar rats treated with aqueous leaf extract of Chasmathera dependens (Hochst) (African Journal of Biomedical Research, 2022)
Chasmanthera dependens (Hochst), a well-known medicinal plant widely used as pain-killer in Africa, however, its effects on fertility has not been fully studied. The effect of aqueous leaf extract of Chasmathera dependens (Hochst) (ALECD) on sperm quality and gonadometric indices of the male Wistar rats was studied. Twenty five adult male Wistar rats were randomly assigned into 5 groups A-E. Groups A-D were orally treated with 25mg/kg, 50mg/kg, 100mg/kg and 200mg/kg of the extract respectively. Group E served as the control and was given only distilled water. The treatment lasted for 21 days after which the rats were humanely sacrificed and samples (blood, semen, testes and epididymis) were collected for laboratory analysis. The treatment did not show any deleterious changes in the haematological parameters studied. There was an increase in sperm motility, livability and sperm count of rats treated with 100 mg/kg. Conversely, there was a decrease in the semen parameters of groups treated with 25 mg/kg, 50 mg/kg and 200 mg/kg of the ALECD. The treatment also caused a significant decrease in the number of morphologically abnormal sperm cells across the groups. There were no significant changes in the testicular and epididymal biometry of the treated rats across the groups.The aqueous leaf extract of Chasmathera dependens possesses fertility enhancing effect at100 mg/kg by improving the semen quality and maintaining gonadometric integrity of male rats. Therefore, the plant can be used to improve the fertility of the male breeding stock at 100 mg/kg body weight.